ANALISIS IMPLEMENTASI BLENDED LEARNING PADA PELATIHAN KEPEMIMPINAN ADMINISTRATOR (PKA) - Eva Novaria (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT This research is motivated by the rapid transition of the state apparatus training system to a blended learning model post-pandemic, which has triggered digital adaptation barriers and doubled the workload for participants. The problem focuses on evaluating blended learning governance policies on the managerial competency achievements of participants in the Administrator Leadership Training (PKA) Batch IV at the BPSDMD of South Sumatra Province in 2025. This qualitative study, using a case study method, collected data from 11 expert informants through in-depth interviews, open-ended questionnaires, naturalistic observation, and analysis of institutional operational documentation. The data analysis stages were carried out using the interactive model of Miles, Huberman, and Saldana, which includes condensation, presentation of narrative descriptions, and drawing conclusions. The research results revealed that the failure to absorb independent material was triggered by weak two-way communication, technical internet network disruptions, and the lack of official duty dispensation at the home office. As a tactical solution, the implementation of the Problem-Based Learning (PBL) model in the classical phase proved superior in boosting leadership behavior quantitatively, with the experimental class achieving an average general attitude score of 3.75 (Very Good), surpassing the conventional class, which only achieved a score of 3.20 (Good). The main conclusion confirms that optimizing blended training requires a formal memorandum of temporary release from official duties to create a conducive learning focus for civil servants. ABSTRAK Penelitian ini dilatarbelakangi oleh transisi kilat sistem kediklatan aparatur negara menuju model campuran (blended learning) pascapandemi yang memicu hambatan adaptasi digital dan beban kerja ganda bagi peserta. Masalah difokuskan pada evaluasi kebijakan tata kelola blended learning terhadap capaian kompetensi manajerial peserta Pelatihan Kepemimpinan Administrator (PKA) Angkatan IV di BPSDMD Provinsi Sumatera Selatan tahun 2025. Studi kualitatif dengan metode studi kasus ini menjaring data dari 11 informan ahli melalui teknik wawancara mendalam, kuesioner terbuka, observasi natural, serta analisis studi dokumentasi operasional lembaga. Tahapan analisis data dijalankan menggunakan model interaktif Miles, Huberman, dan Saldana yang meliputi kondensasi, penyajian deskripsi naratif, serta penarikan kesimpulan. Hasil riset mengungkap bahwa kegagalan penyerapan materi mandiri dipicu oleh lemahnya komunikasi dua arah, gangguan teknis jaringan internet, serta ketiadaan dispensasi tugas kedinasan di kantor asal. Sebagai solusi taktis, penerapan model Problem Based Learning (PBL) pada fase klasikal terbukti unggul mendongkrak perilaku kepemimpinan secara kuantitatif, di mana kelas eksperimen meraih nilai rata-rata sikap umum sebesar 3,75 (Sangat Baik), melampaui kelas konvensional yang hanya mencapai skor 3,20 (Baik). Simpulan utama menegaskan bahwa optimalisasi diklat campuran memerlukan memorandum formal pembebasan tugas jabatan sementara guna menciptakan fokus belajar aparatur yang kondusif.